Heritage value and place identity among local community in relation to the Royal Mausoleum of Kota Tinggi, Johor, Malaysia - Mohd Nashir, Nur Shahida Nasha (2018)
The Royal Mausoleum of Sultan Mahmud Shah is a small and mundane heritage landmark in Johor. However, it represents the history of Sultan Mahmud Shah II, which his decease remarked the end of the glorious dynasty of Melaka Sultanate in Johor heirs background. It is realized through the inheritance of history of the deceased Sultan Mahmud Shah, the Royal Mausoleum creates an identity among the local community towards the place. Place identity is significantly related to the sense of belongingness shaped from one’s memory and perception towards heritage places or objects. The mausoleum has a unique value in term of historical context. However, lack of awareness on heritage building and less in the sense of attachment among the local community towards the Royal Mausoleums may eventually impact on sustainability of the heritage itself as it may not stand as a universal symbolic of pride for the local community and continuity of history may vanished by times. Thus, this research aimed to identify the identity and value of cultural heritage among community in relation to the existence of Royal Mausoleum at Kota Tinggi, Johor using an adopted model by Breakwell’s Theory on Identity which emphasized on continuity, distinctiveness, and self-esteem. Questionnaire survey was conducted to 300 respondents in order to measure the dependency of the place and local identity of the community. The results showed that there was an emotion bonding and memory attachment to the Royal Mausoleum among the local community in the village. The Royal Mausoleum seems to bring back the nostalgia especially among the veteran group of local community. The results confirmed that the sociodemographic background such as education, occupation, and age group mostly influenced the significance of items for place identity, which were ‘distinctiveness’ and ‘self-esteem’. This research contributed in identifying the place identity. Hence, it helped in strengthen the criteria of the Royal Mausoleum to be more presentable as tourist attraction.